DOES GENDER MATTER? EMPATHY AND OLDER ADULTS' HELPING BEHAVIORS IN A DAILY CONTEXT. (11th November 2018) - Huo, M; Graham, J L; Fingerman, K
Abstract: Empathy is a central feature of helping behaviors. Women often report greater empathy than men, but we know little about whether such gender difference in empathy influences the type of help that older women and men provide and the implications of that help. This study used the Daily Experiences and Well-being Study, where older adults (n = 182 women, n = 151 men) rated their empathy, daily support (e.g., emotional, practical, advice), and daily feelings of worry for 5 days. Regardless of gender, more empathic older adults were more likely to provide each type of support than less empathic older adults. Yet, older women experienced greater worry on days when they offered such empathy-based support, whereas this effect was not evident in older men. This study suggests that empathy-based helping may be especially harmful for women's health, which offers new insights into gender disparities in health.